Opuntia ellisiana: Cold Hardiness, Above-Ground Biomass Production and Nutritional Quality in the Mendoza Plain, Argentina (Journal of the Professional Association for Cactus Development, 2003)
Cold damage of Opuntia ellisiana plants obtained by micropropagation was estimated visually after 1- and 2-year growth periods in field conditions. Additionally, the effect of irrigation on above-ground biomass production was evaluated after a 2-year growth period and some parameters related to the nutritional quality of 1-year-growth-period cladodes were determined. Frost damage was estimated visually. Above-ground biomass and stem-area index (SAI) were estimated by regression techniques. One-year-growth plants suffered no frost damage when temperatures dropped to -15°C on two occasions in the winter of 2000. Frost damage reached only 0.9% in 2-year-growth-period plants after freezes of -14.5°C and -13.7°C in the winter of 2001. Irrigation did not have a significant effect on above-ground biomass production. Mean biomass reached 170 kg DM ha-1 after the 2-year growth period. This low production could be explained mainly by the small size of the plant material used for establishing the plantation and the low SAI after the 2-year growth period (0.03). Cladodes of O. ellisiana exhibited crude protein and organic-matter contents of 5.8% and 82.7%, respectively, and an in vitro dry-matter digestibility of 78.3%. Plants of O. ellisiana obtained by micropropagation appear to be tolerant to freezing temperatures attained in areas with extremely cold winters.